Study of surface photovoltage spectrum in p+-GaAs/p-GaAlAs/p-GaAs structures - Jian Liu; Xinlong Chen; Honggang Wang; Yiliang Guo; Yunsheng Qian (Materials Research Express, 2020)
Surface photovoltage (SPV) in p ^+ -GaAs/p-GaAlAs/p-GaAs has been studied by establishing a multilayer model and measuring the SPV at room temperature. The model mainly considers surface recombination velocity, interface recombination velocity and the space charge region (SCR) at the surface of p ^+ -GaAs. The SPV of the multilayer structure is shown to originate predominantly from the minority carrier diffusion, which caused photovoltage between the surface and bottom. Subsequently, the minority carrier diffusion lengths in p ^+ -GaAs and in p-GaAs are obtained from fitting experimental data to the theoretical model. At the same time, the minority carrier diffusion length in p-GaAs is obtained by illuminating the backside (illuminating on p-GaAs) of the p ^+ -GaAs/p-GaAlAs/p-GaAs. The p ^+ -GaAs in p ^+ -GaAs/p-GaAlAs/p-GaAs structure with different thickness are measured to show the variation of SPS with different thickness, but the experimental parameters are not affected. In multi-layer structure, the SPV contributed by different layers has a great difference with different dark saturation current density.